Budgeting practices to improve health system performance An OECD survey of countries from the Latin American and Caribbean region - James, Chris (OECD Publishing, 2019)
This article presents the main findings of two OECD Surveys of Senior Budget and Health Officials conducted in the Latin American and Caribbean region. The surveys help to understand the approaches to budgeting, and take account of the prominent role of agents in the health system across the region, including social health insurance agencies and subnational governments. The focus, however, is on the application of performance-orientated reforms to budgeting, and the extent to which countries in the region have adopted such reforms to improve the efficiency of health expenditure to achieve universal health coverage. The findings point to the use of performance and results-based budgeting in the region, along with new models of provider payment systems integrating performance measures
Keywords: Finance and Investment; Governance; Social Issues/Migration/Health; Economics